A quantum‐chemical DFT study of the mechanism and regioselectivity of the 1, 3‐dipolar cycloaddition reaction of nitrile oxide with electron‐rich ethylenes. Issue 11 (14th November 2017) - Yahia, Wassila; Khorief Nacereddine, Abdelmalek; Liacha, Messaoud; Djerourou, Abdelhafid
Abstract: The 1, 3‐dipolar cycloaddition (13DC) reactions of nitrile‐oxide NO1 with two ethylenes, enamine2a and enamine2b, were computationally studied using B3LYP/6‐31G(d) DFT methods. The two possible ortho and meta regioselective channels were characterized and analyzed. The moderate polarity of these 13DC reactions is related to the high nucleophilic character of both ethylenes, and the moderate electrophilic nature of the NO1, that accounts for the relatively low calculated activation energies. Analysis of different forms of energies along the different reaction channels indicates that the present 13DC reactions are completely ortho regioselective, accordingly to the experimental outcomes. Electron localization function analysis indicates that these 13DC reactions proceed via a nonconcerted (two‐stage) one‐step mechanism. Abstract : The electronic structure changes during the 1, 3‐dipolar cycloaddition reaction of nitrile‐oxide with enamines can be studied by means of first‐principles calculations. Simulations suggest the ortho channels to be more favored than the meta ones. These pathways proceed via a nonconcerted one step two stages mechanism.